2022
DOI: 10.2166/ws.2022.300
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on urban water use: a review

Abstract: The COVID-19 pandemic had significant impact on water utilities, which had to continue providing clean water under safe-distancing measures. Water use patterns were affected, shifting peak demand and changing volumes, though, changes varied from place to place. This study analyses the effects of the safe-distancing measures on water use patterns in different countries and cities with the aim of drawing general conclusions on causes and impacts of changes in water use patterns, as well as providing some insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Data on variations in water demand during lockdowns, cleanliness habits, and increased household activities were taken into consideration to support the 10% rise in water consumption during the pandemic. This estimate was supported by comparisons of pre-and post-pandemic water usage patterns from dependable sources like Alda-Vidal et al [11], Kim et al [12], Jia et al [13], Kasak [14], Sowdy and Hansen [17], Lüdtke et al [19], Kalbusch et al [32], Nemati and Tran [33], Gholami et al [34], Buurman et al [35], and Birisci and Ramazan [36]. The estimation of a hypothetical future outbreak, triggered by the already patented SARS-CoV-3 virus [10], allows for the current simulation with the projection of this higher estimate of 40% per pandemic [11], even though it may currently be deemed improbable.…”
Section: Water Consumption Due To Climate Change-q CCmentioning
confidence: 86%
See 2 more Smart Citations
“…Data on variations in water demand during lockdowns, cleanliness habits, and increased household activities were taken into consideration to support the 10% rise in water consumption during the pandemic. This estimate was supported by comparisons of pre-and post-pandemic water usage patterns from dependable sources like Alda-Vidal et al [11], Kim et al [12], Jia et al [13], Kasak [14], Sowdy and Hansen [17], Lüdtke et al [19], Kalbusch et al [32], Nemati and Tran [33], Gholami et al [34], Buurman et al [35], and Birisci and Ramazan [36]. The estimation of a hypothetical future outbreak, triggered by the already patented SARS-CoV-3 virus [10], allows for the current simulation with the projection of this higher estimate of 40% per pandemic [11], even though it may currently be deemed improbable.…”
Section: Water Consumption Due To Climate Change-q CCmentioning
confidence: 86%
“…The water demand projections, estimating the most significant lower and upper average percentages, are considered for this study at 10% and 40%, respectively, based on previous studies and hypothetical considerations [11][12][13][14]17,19,20,[32][33][34][35][36][37]. The water demand projections, estimating the most significant lower and upper average percentages, are considered for this study at 10% and 40%, respectively, based on previous studies and hypothetical considerations [11][12][13][14]17,19,20,[32][33][34][35][36][37] The number of runs around the median is less than the expected number, indicating some degree of clustering. The number of runs up or down is greater than expected, suggesting some trend or variability in the data series.…”
Section: Water Consumption Due To Climate Change-q CCmentioning
confidence: 99%
See 1 more Smart Citation
“…As an interesting data point, Gholami et al [30] reported an overall increase in water use of 10-15% in different cities across Iran during the COVID-19 pandemic. Buurman et al [31] reviewed the overall evidence of water use changes during COVID-19 and identified changes in daily water demand patterns and that residential water use increased between 6% and 13%, with some changes in the commercial and industrial sectors unclear (although the indications are it was somewhat reduced).…”
Section: What Is Already Known?mentioning
confidence: 99%